نشاطات الشيخ عبد الجبار -رحمه الله- الدعوية وخدماته الاجتماعية: دراسة تحليلية: The activities of Sheikh Abdul Jabbār in Islamic Da’wah and social services: an analytical study - محمد سليم الدين (Al Manhal Research Journal, 2023)
Shah Muhammad Abdul Jabbār was the "Pīr (Spiritual Guide) of Baitush Sharaf", widely known to millions of people in Bangladesh. He was not only an individual, but a holistic non-political institution. He has sacrificed his life to spread Islamic teachings influenced by Sufi Ma'rifah and human welfare. He established many educational institutions and also founded various mosque-based humanitarian projects throughout the country. The main objective of founding "Baitush Sharaf" was to nurture people as real Muslims by training them so that they are able to make a balance between "Zuhd (Asceticism)" and "Being active in this life", between attaining higher humanitarian qualities and having worldly skills. Baitush Sharaf as a center of nourishing spirituality was founded by Sheikh Mīr Muhammad Akhtar, a renowned Muslim saint and spiritual leader. Just before his death, he nominated his prominent spiritual disciple Sheikh ‘Abdul Jabbār as the successor of his noble mission. As a devoted follower, Sheikh Abdul Jabbār continued various Islamic and social welfare activities introduced by his mentor and completed them successfully by the mercy of Allah. As a result he became an ideal for the successors.